Intense chiral signal from α-helical poly-l-alanine observed in low-frequency Raman optical activity. Issue 46 (22nd November 2021) - Yamamoto, Shigeki; Ishiro, Shota; Kessler, Jiří; Bouř, Petr
Abstract : Strong low-frequency Raman optical activity was assigned to helical peptide vibrations. The signal origin was confirmed by DFT. The strength makes these bands suitable for sensitive detection of protein α-helices. Abstract : Raman optical activity (ROA) spectral features reliably indicate the structure of peptides and proteins, but the signal is often weak. However, we observed significantly enhanced low-frequency bands for α-helical poly-l -alanine (PLA) in solution. The biggest ROA signal at ∼100 cm −1 is about 10 times stronger than higher-frequency bands described previously, which facilitates the detection. The low-frequency bands of PLA were compared to those of α-helical proteins. For PLA, density functional simulations well reproduced the experimental spectra and revealed that about 12 alanine residues within two turns of the α-helix generate the strong ROA band. Averaging based on molecular dynamics (MD) provided an even more realistic spectrum compared to the static model. The low-frequency bands could be largely related to a collective motion of the α-helical backbone, partially modulated by the solvent. Helical and intermolecular vibrational coordinates have been introduced and the helical unwinding modes were assigned to the strongest ROA signal at 101–128 cm −1 . Further analysis indicated that the helically arranged amide and methyl groups are important for the strong chiral signal of PLA, while the local chiral centers Cα H contribute in a minor way only. The strong low-frequency ROA can thus provide precious information about the motions of the peptide backbone and facilitate future protein studies.